Implementation of the Search, Solve, Create and Share (SSCS ) Learning Model to Improve Critical Thinking Skills - Efiana, Mia; Jumini, Sri; Parmin, P; Ariyani, Mila (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2025)
Conceptual understanding of science subjects is very important and needs to be instilled and developed in students . The study aims to analyze students' critical thinking skills in learning with the Application of the SSCS (Search, Solve, Create, Share ) learning model . The study uses a quantitative approach, quantitative methods with the type of causality research experiment (cause and effect research). The design used in this True experiment is the pretest-posttest control group design type. The research sample was taken using the simple random sampling method. Critical thinking skills are measured by descriptive questions, and analyzed using a percentage scale. To see the difference in critical thinking skills between the experimental class and the control class, the t-test was used and to see how big the difference was, the Gain test was used. The results of the study showed that the problem-solving abilities of students who used the Application of the SSCS (Search, Solve, Create, Share ) learning model with the t-test results showed that there was a difference in critical thinking skills between the classes that applied and those that did not, indicated by the significance level showing less than 0.05, this means that Ho is rejected and Ha is accepted. This means that there is a difference in the critical thinking skills of students who use the Search, Solve, Create, Share (SSCS) model and those who do not . The difference in students' critical thinking skills is 0.83 with a high category. The impact of learning using critical thinking stages on learning, students are expected to have good critical thinking skills in solving the problems faced well.